What are the risk factors for HIV in men who have sex with men in Ho Chi Minh City, Vietnam?- A cross-sectional study. (December 2016) - Le, Thi; Lee, Patricia; Stewart, Donald; Long, Thanh; Quoc, Cuong
Abstract Background The number of people living with HIV (PLWH) in Vietnam was estimated to rise from 156, 802 in 2009 to 256, 000 in 2014. Although the number of new HIV reported cases has decreased by roughly 14, 000 cases per year from 2010 to 2013 a concerning increase in HIV prevalence has been identified among men who have sex with men (MSM) from 1.7 % in 2005 to 2.4 % in 2013. There are signs of increased HIV (+) prevalence among MSM in a number of cities/provinces, especially in the two largest cities, Ho Chi Minh City (HCMC) and Hanoi. HCMC is the country's major "hot spot" for HIV/AIDS, with over a third of the total national AIDS patients. This paper is based on a secondary analysis of Integrated Biological and Behavioural Surveillance (IBBS) data collected in Vietnam in 2009 to examine the research question "Do behavioural risk factors contribute to HIV infection among the MSM population in HCMC?". Methods A cross-sectional design was employed to sample males aged over 15 from communities in HCMC, who reported having any types of sex with another man at least once during the last 12 months. Participants (399) were recruited using the respondent driven sampling (RDS) method and provided both biological data (specimens) and behavioural data collected through a questionnaire survey. Results The study found high HIV prevalence (14.8 %) among the MSM sample from HCMC. Multivariate analysis found age and level of formal education completed, to be significantly associated with HIV infection. MSM aged over 25 were more likely to be HIV (+) than the younger group (OR = 7.82, 95 %CI = 3.37–18.16, p < 0.001); as were participants who had low educational (OR = 2.74, p < 0.05) and medium educational levels (OR = 2.68, p < 0.05). In addition, those participants who had anal sex with male partners (OR = 2.7, p < 0.05) and whose sexual partners injected drugs (OR = 2.24, p < 0.05) and who felt at risk of HIV infection (OR = 2.42, p < 0.01) had a higher risk of HIV infection. Conclusions The high proportion of HIV (+) MSM in our sample from HCMC indicates that we need a better understanding of MSM behaviour patterns, risk practices and social networks as well as improved HIV prevention and control measures. More targeted and relevant HIV prevention programs for older and less educated MSM are urgently needed to address the key risk factors we have identified. MSM engaging in drug-related risk behaviours require multi-strategy HIV interventions relating to both sex and drug behaviour among MSM and their partners who engage in drug use. Further work is needed to identify locations and strategies where these high-risk individuals can be accessed as well as to reduce barriers related to social discrimination and stigma. Targeting high risk individuals and groups should supplement existing efforts aimed at the MSM population in HCMC.